2009
DOI: 10.1111/j.1574-6976.2008.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA viruses in the sea

Abstract: Viruses are ubiquitous in the sea and appear to outnumber all other forms of marine life by at least an order of magnitude. Through selective infection, viruses influence nutrient cycling, community structure, and evolution in the ocean. Over the past 20 years we have learned a great deal about the diversity and ecology of the viruses that constitute the marine virioplankton, but until recently the emphasis has been on DNA viruses. Along with expanding knowledge about RNA viruses that infect important marine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 248 publications
2
101
0
Order By: Relevance
“…Recent work has shown that the number of viruses within the oceans is far larger than only recently could have been imagined (41). It is therefore probable that many alphaviruses like the louseborne SESV remain to be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that the number of viruses within the oceans is far larger than only recently could have been imagined (41). It is therefore probable that many alphaviruses like the louseborne SESV remain to be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Although less abundant than prokaryotes, the relatively high number of viruses released per eukaryotic cell (reviewed by Lang et al, 2009) may increase representation of their viruses in the oceans such that they could comprise a significant portion of non-tailed viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Most aquatic bacteriophages are nonenveloped, but the ocean also appears to have abundant RNA viruses that infect eukaryotes (41). Some of these are enveloped (16). If the pattern of results from this study with four fish viruses extends to all viruses, the addition of Corexit 9500 to an aquatic environment might be expected to reduce enveloped viruses while allowing nonenveloped viruses to endure or be activated.…”
Section: Discussionmentioning
confidence: 97%
“…These bacteriophages or phages influence the microbial loop and ultimately global biogeochemical cycles (15). Although greatly outnumbered by phages, viruses that infect algae and aquatic animals are also in the sea and freshwater (16,17). Whether from prokaryotes or eukaryotes, viruses have common structural themes.…”
mentioning
confidence: 99%